Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif Pada Materi Bulutangkis Di MAN 1 Medan - Rio Ferdinan Nababan; Iradat Lidwina Mendrofa; Rahmat Alwi Nasution (CV. ULIL ALBAB CORP, 2024)
This study aims to develop interactive multimedia learning media for badminton material at MAN 1 Medan and evaluate its effectiveness on students' understanding. The research design employed is quasi-experimental, utilizing pretest and posttest methods, involving 30 eleventh-grade students as the sample. Data were collected through a pretest to measure students' initial understanding, followed by the implementation of interactive learning media, which includes demonstration videos, practice simulations, interactive quizzes, and 3D animations. After the learning process, a posttest was conducted to assess the improvement in students' understanding. Additionally, interviews were conducted to gather students' feedback on the learning media used. The results indicate a significant improvement in students' understanding of badminton techniques, with 90% of students stating that the learning media was easy to understand and 85% finding it engaging. This study concludes that interactive multimedia learning media can enhance students' understanding and motivation in learning badminton. The findings are expected to contribute to the development of more effective teaching methods in the field of physical education and health.